Finite Volume Element Approximation for the Elliptic Equation with Distributed Control - Quanxiang Wang; Tengjin Zhao; Zhiyue Zhang (International Journal of Differential Equations)
In this paper, we consider a priori error estimates for the finite volume element schemes of optimal control problems, which are governed by linear elliptic partial differential equation. The variational discretization approach is used to deal with the control. The error estimation shows that the combination of variational discretization and finite volume element formulation allows optimal convergence. Numerical results are provided to support our theoretical analysis.